A fast decomposition algorithm of positive and negative sequence components with sampling noise optimization. (November 2022) - Ma, Mingyao; Liang, Jiacheng; Xiang, Nianwen; Wang, Hanyu; Wu, Jijun
Abstract: In this paper, a fast decomposition algorithm of positive and negative sequence components is derived first. And based on analyzing the interaction between sampling noise and time (angle) delay, a sampling-noise-optimized decomposition algorithm is proposed. This optimized method can identify positive and negative sequence components quickly and limit the error caused by sampling noise. Compared with existing methods, the new algorithm has a rapid response speed and greatly reduces the sampling noise level under the same response time. Therefore it is more suitable for those time-critical applications. Simulation results are in correspond with analytical conclusions and the validity of the method is examined. Highlights: Noise-optimized fast decomposition method of positive & negative sequence components. Faster response speed and relatively lower sampling noise level. A generic algorithm for different time-critical applications.